الأثر التراكمي لرأس المال الثابت في سورية وعلاقته بالناتج المحلي الصافي دراسة تحليلية إحصائية خلال الفترة 1990-2009 - النعيمي قاسم; العدي إبراهيم; رجوب ابتسام علي (Latakia University Journal - Economic and Legal Sciences Series, 2019)
نتناول في هذا البحث الأثر التراكمي لرأس المال الثابت في سورية وعلاقته بالناتج المحلي الصافي كدراسة تحليلية إحصائية خلال الفترة 1990-2009، وباستخدام البرنامج الإحصائي SPSS قمنا ببناء نماذج إحصائية صالحة للتنبؤ بالناتج المحلي الصافي في الفترة المقبلة، هذا وقد توصلنا إلى مجموعة من النتائج المهمة من بينها وجود علاقة بين الناتج المحلي الصافي ومجمل تكوين رأس المال الثابت في كل من القطاعين العام والخاص وقطاعات الاقتصاد الوطني (الزراعة، الصناعة والتعدين، النقل والمواصلات، دور السكن، قطاعات أخرى)، بالإضافة إلى الزيادة الملحوظة لمساهمة القطاع الخاص في مجمل تكوين رأس المال الثابت، والتذبذب في توزيع مجمل تكوين رأس المال الثابت بين الأنشطة الاقتصادية. This study tackles the cumulative effect of fixed capital in Syria and its relationship to net gross domestic product analyzing certain statistics during the period 1990-2009. Using the statistical program SPSS, we have built statistical models that can predict gross domestic net in the coming period. We have reached a number of important results: there is a relationship between Net Gross Domestic Product and total fixed capital formation in both the public and private sectors of the national economy (agriculture, industry, mining, transport and communication, the role of housing, and other sectors. In addition, there is a significant increase in the contribution of the private sector in total fixed capital formation , and there is a fluctuation in the distribution of the total fixed capital formation among economic activities.